Ethical Theory and Moral Practice at 24 - Radoilska, Lubomira (Ethical theory and moral practice, 2021)
This Editorial outlines recent developments in the Journal’s scope, mission and review policy. It also illustrates the range of topics addressed on the pages of Ethical Theory and Moral Practice, which is now entering its 24th year.